Previous Criminal Behaviour as Predictor of Serious Offences - Glomazić, Hajdana; Mikić, Andrijana; Sviličić, Nikša (Zbornik Instituta za kriminološka i sociološka istraživanja, 2015)
In an attempt to respond to the central question of our research – whether previous criminal behaviour is a predictor of serious crimes – we have analysed the criminal behaviour of convicts on the death row in the state of Texas, in the United States, from 1976 to June 2014. Bearing in mind the whole context of criminal behaviour that preceded the death penalty, we decided to put the objective of our research on providing an answer to the question whether a correlation between these variables exists, and if it does, what is the nature of their correlation. To identify predictors, univariate and multivariate binary logistic regression were used. The results have shown that almost half of criminal offences are committed by returnees, and that the previous criminal behaviour is a significant predictor of serious crimes such as murder and rape.